2020
DOI: 10.1186/s13011-020-00285-3
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorders in Saudi Arabia: a scoping review

Abstract: Background: Substance use disorders (SUD) are mental health conditions that arise from chronic drug use. There is an increased recognition of this problem in Saudi Arabia. Objective: Conduct a comprehensive review of published literature on SUD to identify knowledge gaps and to guide future research. Methods: PubMed, Embase and Cochrane databases were searched with suitable keywords for SUD publications up to June 10, 2019. Eligible studies (primary research conducted in Saudi Arabia) were organized into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…Multiple studies have been conducted into SUD, with approximately 8% of Saudis having abused substances, most commonly, amphetamines. [16] Another study reported that 13% of the worldwide population suffers from SUD. [17] Lambert et al indicate that 74% of those with SUD will experience a psychotic episode.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted into SUD, with approximately 8% of Saudis having abused substances, most commonly, amphetamines. [16] Another study reported that 13% of the worldwide population suffers from SUD. [17] Lambert et al indicate that 74% of those with SUD will experience a psychotic episode.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that the Saudi authorities consider to include opiate-and opioid-based pharmaceutical medicines in their prevention, pharmacovigilance, and harm minimization strategies. There is growing national level recognition of the complexities of addressing drug dependence and related comorbidities (Al Harbi, 2017;Ibrahim et al, 2018;Katselou et al, 2016;Saquib et al, 2020). While opioid use is most prevalent in drug treatment patient populations (Alshomrani et al, 2017), we recommend that addiction treatment systems in Saudi Arabia now diversify to recognize and support individuals with codeine dependence and work hand in hand with pain management clinics.…”
Section: Percentagementioning
confidence: 99%
“…Research on pain management and patient care (particularly those with non-cancer musculoskeletal pain), prescribing rates of opioids, and consumption trends, are scarce in the Middle East (Cleary et al, 2013;Wilby & Wilbur, 2017). We report here from the Kingdom of Saudi Arabia (hereafter Saudi Arabia), a high income Islamic country, which has experienced rapid societal change with increased drug consumption patterns (including amphetamine type stimulants, cannabis, heroin, and cocaine) in recent years (Abomughaid et al, 2018;Abualola & Rahamathulla., 2017;Alhazmi et al, 2020;Kravitz & Nichols, 2016;Saquib et al, 2020; United Nations Office on Drugs and Crime 2020). Very little is known however regarding pain management, prescribing trends, and patient misuse of opioids (tramadol is most commonly prescribed) in Saudi Arabia (Alharbi et al, 2020;Al-Rowaili et al, 2009;AlRuthia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Amphetamine is a synthetic drug that directly and indirectly influences the CNS and subsequently affects the peripheral organs [ 4 ]. It is the most common drug addiction in Saudi Arabia in the last two decades [ 5 ]. Amphetamine is a CNS stimulant; it appears to increase concentration, wakefulness, mood, and physical performance which lead to widespread use by students, academics, and medical professionals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%